Production of lentivirus carrying green fluorescent protein with different promoters for in vitro gene transfer - Ngai, Siew Ching; Rajesh, Ramasamy; Abdullah, Syahril (Universiti Putra Malaysia Press, 2012)
Many diseases are potential targets for gene therapy using either non-viral or viral vectors. Unlike non-viral methods, viral vectors, such as lentiviruses, have the ability to integrate into the host chromosome, which can lead to long-term transgene expression. Lentiviruses have advantages over other types of viruses due to their capacity to transduce non-dividing cells. An optimized generation of lentiviruses carrying green fluorescent protein (GFP) reporter gene driven by either UbC (LV/UbC/GFP) or CMV (LV/CMV/GFP) promoter is described in this paper. The lentiviruses were produced by co-transfecting lentiviral expression constructs and packaging mix into 293FT lentivirus producer cell lines. Lipofectamine was highly efficient in transfecting the cells compared to Transfast and Polyethyleneimine (PEI). Following cell transfection, syncytia were clearly visible at day 2. Lentiviruses were harvested at days 1, 2 and 3 post-transfection. The highest transduction efficiency was read from LV/CMV/GFP harvested at day 2 post-transfection and LV/UbC/GFP harvested at day 3 post-transfection. Finally, the GFP expression in COS-7 cells was determined at day 2 and day 14 post-transduction for transient and stable GFP expression. It was found that the GFP expression declined overtime. However, the transduction efficiency and duration of the transgene expression in COS-7 cells transduced with LV/CMV/GFP were higher compared to LV/UbC/GFP. In conclusion, we have successfully produced lentiviruses carrying GFP with different promoters and shown that the viruses were able to infect COS-7 cells at different efficiencies. Meanwhile, the generation of the active lentiviruses will allow us to the subsequent analysis of the effect of regulatory elements in future study.